1998
DOI: 10.1046/j.1432-1327.1998.2570142.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and molecular cloning of porcine intestinal glycerol‐ester hydrolase

Abstract: A glycerol-ester hydrolase was purified to homogeneity from porcine intestinal mucosa using a partial delipidation method and an eight-step purification procedure. The isolation scheme used gave a 483-fold purification, resulting in a pure enzyme with a specific activity on tributyrin of 290 µmol · min Ϫ1 · mg Ϫ1 . The molecular mass of the enzyme was estimated at 240 kDa, based on the results of size-exclusion chromatography, and at 60 kDa, as determined by SDS/PAGE analysis. The isoelectric focusing data obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 25 publications
4
27
0
1
Order By: Relevance
“…[1] So far, PLE can only be obtained by the extraction of pig liver with organic solvents and, as a consequence, an illdefined preparation is provided. [6] This hydrolase was found to share as much as 97 % amino acid sequence identity with that reported by Matsushima et al [4] We now describe for the first time the cloning and functional expression of a PLE subunit ± -which represents the major esterase in commercial PLE preparationsÐin the methylotrophic yeast Pichia pastoris. [2] Some fractions separated by isoelectric focusing preferred methyl butyrate or butanilicain (N-butylglycyl-2-chloro-6-methylanilide hydrochloride), whereas others hydrolyzed butyrylcholine and proline-bnaphthylamide with high activity.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…[1] So far, PLE can only be obtained by the extraction of pig liver with organic solvents and, as a consequence, an illdefined preparation is provided. [6] This hydrolase was found to share as much as 97 % amino acid sequence identity with that reported by Matsushima et al [4] We now describe for the first time the cloning and functional expression of a PLE subunit ± -which represents the major esterase in commercial PLE preparationsÐin the methylotrophic yeast Pichia pastoris. [2] Some fractions separated by isoelectric focusing preferred methyl butyrate or butanilicain (N-butylglycyl-2-chloro-6-methylanilide hydrochloride), whereas others hydrolyzed butyrylcholine and proline-bnaphthylamide with high activity.…”
Section: Introductionsupporting
confidence: 58%
“…As already outlined in the introduction, two groups reported the cloning of putative pig liver [4] or intestinal [6,12] esterase genes, but they did not report the functional expression of active enzymes. Initially, we also failed in functional expression of PLE in either E. coli or P. pastoris, despite the use of various plasmid constructs and replacement of the 18 amino acid N-terminal leader sequence of PLE with the ompA signal sequence or the afactor leader sequence, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although these enzymes are yet to be characterized, various esterases with sequence identities to PMPMEase in excess of 70% have been reported from the intestines [29], human brain [30], human alveolar macrophages [31], human monocytes and macrophages [31, 32]. …”
Section: Discussionmentioning
confidence: 99%
“…Two carboxylesterases have been identified in the pig, and they have been classified as CES1 and CES (Satoh and Hosokawa, 2006). David et al (1998) reported a pig intestinal carboxylesterase that showed high similarity with that of rat and human intestinal carboxylesterases. Clark et al (1993) and Hewitt et al (2000) showed that esters applied to the skin surface were hydrolyzed during dermal absorption using skin in vitro in a diffusion cell.…”
mentioning
confidence: 99%